Advanced Control in a Delayed Coking Furnace. (March 2015) - Su, Chengli; Shi, Huiyuan; Li, Ping; Cao, Jiangtao
This article reports an industrial application of advanced control in a delayed coking furnace unit. The advanced control is required because of the semi-batch and semi-continuous nature of the unit. The traditional proportional–integral–derivative control has been proven not sufficient and capable for this particular petro-chemical process. The advanced control is formed by integrating a predictive functional controller with a traditional proportional–integral–derivative controller in cascade architecture with a feed-forward compensator designated for disturbance rejection. The advanced control system is implemented in a Yokogawa CS3000 integrated production control system. The application results indicate that the advanced control can significantly improve the performance of the delayed coking furnace unit in terms of the outlet temperature of furnace and oxygen concentration of the chimney.